Paradigma italijanskog društva u romanu "Messinske žene" Elia Vittorinia / A paradigm of the Italian society in the women of Messina By Elio Vittorinia - Mejdanija, Mirza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The Women of Messina by the Italian author Elio Vittorini was published in 1964 and belongs to the prose of neorealism. In this novel, the author depicts the period after the Second Word War, and later, the economic boom in Italy as well. The Italy emerging after the Second Word War is in catastrophic spiritual and material circumstances. The war left the country in severe moral and political disintegration. Italy had been conquered and occupied by the military, depending on the support of the Allies and was, therefore, unable to completely govern its own destiny. The post-war period of Italian rebirth is ending at the end of 1950s and the beginning of 1960s. An era of a new industrial revolution begins and the country starts living a new reality, as the one seen in modern and developed countries. The Italian 'economic miracle', i.e. the so-called 'economic boom' of the 1950s and 1960s, is the period of a great economic growth and industrial development with Italy as its protagonist. The econimic and industrial advancement is thus changing the living conditions, but also the relations within the society, as well as the etuquette and the mindset. In The Women of Messina, Vittorini is trying to join his own lyricism with the historical events which he strives to portray in their very essence. In this novel, the author is experimenting with a choral narrative of an epic scope and the fresco of Italy's rebirth after the period of the Second Word War. The novel tells a story of Uncle Agrippa who is looking for his own daughter by travelling throughout Italy on a train while she, Siracusa, not even knowing that her father is looking for her, spends time with Ventura, her lover. However, more dominant is the story about a utopian community established by a group of immigrants, Ventura and Siracusa among them, which symbolocally represents a resurrection of humans after a tragedy of war. These three narrative flows function within the novel as individual stories that overlap at times. The novel embodies a new mode of transposition in time; the transfer from the post-war years into 1960s is sudden and abrupt and there are no fractures in the narrative between the two periods. The novel transfers from the myth of a peasant civilisation into a criticism of an industrial society.